Quality Environments in Early Childhood - Valverde Forttes, Paz (Pensando Psicología, 2015)
Purpose: The objective of the article is to share some of the experience of Chile in relation to the search for and creation of quality environments that would favor learning and development among children between zero and six years of age.Topic: The promotion of quality environments based on the pedagogical intention of educators, to organize time, space and interactions, promoting learning among boys and girls.Development: This involves a mainly descriptive exposition of the Chilean context and other results obtained through the available evaluations based on the application of two instruments: ecers-r and iters-r, and class, in the framework of the implementation of programs aimed at improving quality, such as Quik and Un Buen Comienzo de la Fundación Oportunidad.Conclusions: These results demonstrate the importance of the topic and an analysis is made of emerging public policies and the challenges or tensions that persist. These include the tension between quality and coverage, along with the problem of distrust among the actors involved about the significance and reality of a quality education
Keywords: learning; childhood development; evaluation